Normal people - Rooney, Sally (Faber & faber, 2018)
The feverishly anticipated second novel from the young author of 2017's most acclaimed debut Conversations with Friends. Connell and Marianne grow up in the same small town in rural Ireland. The similarities end there; they are from very different worlds. When they both earn places at Trinity College in Dublin, a connection that has grown between them lasts long into the following years. This is an exquisite love story about how a person can change another person's life - a simple yet profound realisation that unfolds beautifully over the course of the novel. It tells us how difficult it is to talk about how we feel and it tells us - blazingly - about cycles of domination, legitimacy and privilege. Alternating menace with overwhelming tenderness, Sally Rooney's second novel breathes fiction with new life --